The Influence Of Customer Trust On Customer Satisfaction Through Word Of Mouth At PT Asoka Perkasa Kemala Cipta - Fitri Karnila; Muchsin Saggaf Shihab (Jurnal Scientia, 2024)
The increasingly rapid development of business strategies using marketing communications in this era of globalization has led companies to carry out direct marketing using Outdoor Media Advertising services. PT Asoka Perkasa Kemala Cipta is a company operating in the field of outdoor media advertising services which is required to face quite tight competition with other similar companies. This research aims to determine the effect of customer trust on customer satisfaction through word of mouth at PT Asoka Perkasa Kemala Cipta. This type of research is quantitative research. The data presented in this research was obtained through a questionnaire distributed to 100 respondents. Statistical analysis uses the Smart-PLS method to test models and hypotheses. The results of this research show that customer trust has a positive and significant effect on customer satisfaction. Customer trust has a positive and significant effect on word of mouth. Customer satisfaction has a positive and significant effect on word of mouth.